Best Practice in AIDS Prevention and Mitigation - World Bank (Washington, DC, 2012)
To gather information on special population groups pregnant women, military men, truck drivers, sex workers through testing for common STDs and making inquiries regarding sexual practices and attitudes using a rapid assessment methodology. The studies: (i) are the first ever reliable source of STD prevalence data in these countries, (ii) raise awareness of policy-makers as to the magnitude of common STDs and unsafe sexual behavior among certain population groups, (iii) validate STD treatment guidelines, (iv) increase capacity in clinical and epidemiological skills, and (v) help to effectively treat study participants for common STDs. These studies, although simple and rapid in design compared to community-based household surveys, are still a challenge to perform in the low resource setting of most African countries. Ensuring high quality standards for laboratory testing and adequate supplies of drugs, and mobilizing truck drivers and sex workers requires a high degree of planning and resourcefulness.